PARAMETRIC SYNTHESIS OF STATICLY DETERMINED SPATIAL MECHANISMS OF BENDING MACHINES - ZALYUBOVSKYI, MARK; ZAYIKA, OLEKSIY; KOSHEL, OLEXANDR; KOSHEL, GANNA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The problem of static uncertainty is described, which is characteristic of hinged spatial mechanisms, in particular, spatial mechanisms of felting machines. The problem of static uncertainty consists in the presence of a passive (redundant) connection in the kinematic chain of the spatial mechanism, which negatively affects the operational characteristics of the technological equipment. A parametric synthesis of statically determined spatial mechanisms of machines with complex spatial movement of working containers with different design features was carried out. These machines are used to implement felting technological operations. The parametric synthesis was carried out in order to further expand and diversify the functional properties of the rolling equipment, in general. It is noted that the degree of mobility of hinged mechanisms leads to the emergence of an additional component of the movement of its movable links between themselves with the corresponding amplitude. Relationships between the change in the interaxial distance of the shafts installed in the frame, as well as the amplitude of movement of the moving links of the spatial mechanisms of the rolling machines, have been established. Mathematical dependencies for the possibility of rational calculation of the main geometric and structural parameters of synthesized statically defined spatial mechanisms, as well as mathematical dependencies for calculating the amplitude values of the movement of the corresponding links, were obtained. The classification of spatial statically determined joint mechanisms of the rolling machine and general approaches to their comprehensive analytical study from the point of view of calculating their geometric and structural parameters have been developed. The obtained results of analytical studies can be used by specialists of the design offices of the relevant machine-building enterprises, which are engaged in the design of rolling and mixing equipment.